Application of Phytoremediation in Restoring Sustainable Development to the Environment: Economic and Soil Conditions; Ekonomiczne i glebowe uwarunkowania zastosowania fitoremediacji w przywracaniu zroẃnowazȯnego rozwoju sŕodowiska - Wiktor Pszczoĺkowski; Zdzisława Romanowska-Duda; Agata Pszczoĺkowska; Mieczysław Grzesik; Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
The objective of this article is a presentation of priority questions and relations involving economic and soil conditions for the application of phytoremediation technology in restoring sustainable development to the environment. The analysis looks at the justifiability of the application of phytoremediation in restoring a balanced environment as an alternative method to costly land recultivation aimed at eliminating pollutants-a solution that is impossible in the case of large areas. The cost effectiveness of the use of phytoremediation in the recovery of trace element in the soil through the process of phytoremediation was demonstrated. The quality of soils as found in the Voivodeship of Łod́zẃas analyzed from the point of view of potential application of the phytoremediation method, taking into account subdivision by heavy metals found in the soils as well as their origins and properties. Grades of soil purity are presented and border values of heavy metal content were identified. – – Celem niniejszego artykułu jest przedstawienie priorytetowych zagadniení powiazan\', dotyczacych ekonomicznych i glebowych uwarunkowanźastosowania technologii fitoremediacji w przywracaniu zroẃnowazȯnego rozwoju sŕodowiska. Analizie poddano zasadnosćśtosowania fitoremediacji w przywracaniu zroẃnowazȯnego sŕodowiska jako metody alternatywnej do kosztownej rekultywacji terenoẃ w celu usuwania zanieczyszczen\', ktoŕe jest niewykonalne do przeprowadzenia na duzẏch areałach. Wykazano opłacalnosćśtosowania fitoremediacji w odzyskiwaniu pierwiastkoẃ sĺadowych z gleby w procesie phytominingu. Przeanalizowano jakosćǵleb wystepujacych w wojewod́ztwie łod́zkim w aspekcie potencjalnego zastosowania metody fitoremediacji z uwzglednieniem podziału metali ciezk̇ich zawartych w glebach uwzgledniajacy ich pochodzenie oraz własćiwosći. Przedstawiono klasy czystosći gleb i wyznaczone w nich graniczne zawartosći metali ciezk̇ich.
Keywords: 330